Non-invasive early diagnosis of oral squamous cell carcinoma using piezoelectric biosensor - Irene E. Rieuwpassa; Yu-Ri Kim; Megatriani Matandung; Gabriel SA. Matongan; Sumintarti (Journal of Dentomaxillofacial Science, 2020)
Objective: To develop a device capable of distinguishing Oral squamous cell from other types of lesion so early diagnosis can be made non-invasively. Methods:The piezoelectric buzzer was coated with IgA EBV enzyme conjugate and antigen substance from Bionevan. The sensor was designed label free so further substance won’t be needed. The body of the device was made from white acrylic with 4mm thickness. The body was divided into 3 compartments each with different purpose. The main component consists of reagent coated piezoelectric buzzer and sensor. Both sensors are attached to Arduino UNO, breadboard, LIPO UBEC battery and LCD display network. The arduino UNO will read and process the difference between initial frequency and vibration frequency after the antigen were bind by the reagent, and shows the level of IgA in the LCD display.Results: The device worked and manage to show the level of IgA and presence of EBV in saliva but still need further improvement to make it more specific and validConclusion: Piezoelectric biosensor have shown promise to make early non-invasive diagnosis for OSCC